Distinct impacts of bi‐allelic WNT10A mutations on the permanent and primary dentitions in odonto‐onycho‐dermal dysplasia. Issue 1 (20th December 2018) - Yu, Miao; Liu, Yang; Liu, Haochen; Wong, Sing‐Wai; He, Huiying; Zhang, Xiaoxia; Wang, Yue; Han, Dong; Feng, Hailan
Abstract: Odonto‐onycho‐dermal dysplasia (OODD) is a rare autosomal recessive syndrome characterized by multiple ectodermal abnormalities. Mutations of the wingless‐type MMTV integration site family member 10A ( WNT10A ) gene have been associated with OODD. To date, only 11 OODD‐associated WNT10A mutations have been reported. In this report, we Characterized the clinical manifestations with focusing on dental phenotypes in four unrelated OODD patients. By Sanger sequencing, we identified five novel mutations in the WNT10A gene, including two homozygous nonsense mutations c.1176C>A (p.Cys392*) and c.742C>T (p.Arg248*), one homozygous frame‐shift mutation c.898‐899delAT (p.Ile300Profs*126), and a compound heterozygous mutation c.826T>A (p.Cys276Ser) and c.949delG (p.Ala317Hisfs*121). Our findings confirmed that bi‐allelic mutations of WNT10A were responsible for OODD and greatly expanded the mutation spectrum of OODD. For the first time, we demonstrated that bi‐allelic WNT10A mutations could lead to anodontia of permanent teeth, which enhanced the phenotypic spectrum of WNT10A mutations. Interestingly, we found that bi‐allelic mutations in the WNT10A gene preferentially affect the permanent dentition rather the primary dentition, suggesting that the molecular mechanisms regulated by WNT10A in the development of permanent teeth and deciduous teeth might be different.